The Importance of Rural Social Productive Space to Increase the Social Capital of Agribusiness Community in Agropolitan Area - Deden Syarifudin; Riza Fathoni Ishak (Jurnal Wilayah dan Lingkungan, 2020)
Agropolitan area is a concept of functional space based on agricultural production, which requires a specific population density as a capital for the productivity of the rural regions with the support of urban utilities and social infrastructure/social space. Weak social capital makes the agropolitan area grow slowly. This is the impact of unplanned productive social space as a vehicle for social capital’s growth implemented in regional plans. However, social interactions occur if the social infrastructure is well articulated in creating spatial productivity, production, and multiphase inheritance for the sustainability of agribusiness activities. This study aims to identify the importance of social productive space in the form of social infrastructure to increase the social capital in agropolitan area. The method used is a case study to observe social processes that occur from time to time, supported by in-depth interview. The results indicate a typology of social capital that is not formed instantly, but contains a long history over time due to the repetition of interaction between communities in social spaces that are not technically constructed and unplanned in the agropolitan area spatial planning. This productive space is a place to build social closeness through repetition of interaction, sharing, knowledge transfer, equalization of perceptions involving residents, and collaboration between individuals and groups. The productive space in the form of social infrastructure consists of mosques, sports fields, markets, community meeting rooms (bale), business group rooms, and farmer groups. Therefore, the plan document must consider the functioning of social space and adaptive social space based on IT connections (cafes, sports clubs, open spaces, bale, and mosque grounds) into agropolitan spatial planning.